Design and analysis of metamaterial antenna using triangular resonator - A. Rahim, Mohamad Kamal (2012)
In this paper, a metamaterial antenna consisting of Triangular resonator (TR) and a thin wire (TW) is proposed. The antenna is excited through a single unit cell left Handed Materials (LHM) which act as the main radiating element via coplanar waveguide (CPW) transmission line. The Left Handedness of the unit cell is investigated and verified. The simulated return loss shows that a bandwidth of 58% is achieved over a frequency band of 6.42-11.23 GHz at a return loss of -10dB. The maximum gain of 4.45 is obtained at a frequency of 10.32GHz. Simulated and measured return loss shows an agreement while the radiation pattern is Omnidirectional.